2(2x-i)4x-6x=

Simple and best practice solution for 2(2x-i)4x-6x= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(2x-i)4x-6x= equation:


Simplifying
2(2x + -1i) * 4x + -6x = 0

Reorder the terms:
2(-1i + 2x) * 4x + -6x = 0

Reorder the terms for easier multiplication:
2 * 4x(-1i + 2x) + -6x = 0

Multiply 2 * 4
8x(-1i + 2x) + -6x = 0
(-1i * 8x + 2x * 8x) + -6x = 0
(-8ix + 16x2) + -6x = 0

Reorder the terms:
-8ix + -6x + 16x2 = 0

Solving
-8ix + -6x + 16x2 = 0

Solving for variable 'i'.

Move all terms containing i to the left, all other terms to the right.

Add '6x' to each side of the equation.
-8ix + -6x + 6x + 16x2 = 0 + 6x

Combine like terms: -6x + 6x = 0
-8ix + 0 + 16x2 = 0 + 6x
-8ix + 16x2 = 0 + 6x
Remove the zero:
-8ix + 16x2 = 6x

Add '-16x2' to each side of the equation.
-8ix + 16x2 + -16x2 = 6x + -16x2

Combine like terms: 16x2 + -16x2 = 0
-8ix + 0 = 6x + -16x2
-8ix = 6x + -16x2

Divide each side by '-8x'.
i = -0.75 + 2x

Simplifying
i = -0.75 + 2x

See similar equations:

| 4a+2b-6a+3a= | | 37.12=8g+3.84 | | (x-8)2/3=4 | | 5y+30=3x | | 3x-6/4=12 | | v^2-2v-5=0 | | 545/5 | | y/0.5=-6 | | 2x+(-3)=9 | | log(x+6)-log(6)=log(12) | | ln(3x)=x-4 | | y/.5=-6 | | 2ln(x+4)=4 | | -(7-8A)-(2+7A)-27=-(3-7A)+(-A)+2 | | 2(2x-i)-4x-6x= | | 5*3/5x-5*6 | | 9x^4-18x^2+5=0 | | 4r^3=72 | | 1/2x2/7= | | 4c=54 | | 1.3x+2.1=5.7 | | 24+4b=8 | | 17.64*8= | | 7(8)=56 | | 81x^2+1=101 | | a=3*w | | (-7xz^5/y)^3 | | -4(3+4n-3m)= | | -4.5-1.3+4.5= | | Log(x+4)+log(4x+3)=2log(2x) | | 2250/2= | | 14m-3n-2m+5n= |

Equations solver categories